Impact of Marriage on Performance, Behavior, and Work-Life Changes among Female Employees in the Health Sector: Impact of Marriage in the Health Sector - Khuhro, Naheed; Veesar, Ghulam Yaseen; Tareen, Najeeb Ullah; Ahmad, Farah; Shams, Surraya (Pakistan Journal of Health Sciences, 2025)
According to the World Bank, only 20% of Pakistani women hold a university degree linked to professional employment. Furthermore, women’s participation across all sectors remains notably low, with figures below 5%. Objective: To assess the variations experienced by married female employees within the healthcare sector. Specifically, it investigates the changes in performance, WLB, and PB as perceived by the participants after marriage. Methods: This survey was conducted over the period of 01 years from public and private organization where women practitioner was working as doctor or postgraduate students affiliated with the College of Physicians and Surgeons of Pakistan (CPSP) or General Practitioners (GPs) within the province of Sindh. Results: The paired sample t-test also reveals a statistically significant difference between Work-Life Balance of Before-Marriage Status (mean = 2.0961, SD = 0.61938) and After-Marriage Status (mean = 2.2167, SD = 0.66697), with the difference t (203) = -3.070, p = 0.002 (two-tailed), α = .05 and finally there was a significant difference between Professional Behavior of before and after marriage (mean = 1.8255, SD = 0.63691), (mean = 1.9382, SD = 0.70962); t (203) = -2.917, p = 0.004 (two-tailed), α = .05 respectively. Conclusion: This study highlighted the significant impact of marital status changes on women’s professional lives, particularly in the health sector.